Automatic segmentation of the cerebellum in ultrasound volumes of the fetal brain - Velásquez Rodríguez, G.; Arámbula Cosío, F.; Guzmán Huerta, M. E.; Camargo Marín, L.; Borboa Olivares, H.; Escalante Ramírez, B. (Revista Mexicana de Ingenieria Biomedica, 2015)
The size of the cerebellum in ultrasound volumes of the fetal brain has shown a high correlation with gestational age, which makes it a valuable feature to detect fetal growth restrictions. Manual annotation of the 3D surface of the cerebellum in an ultrasound volume is a time-consuming task, which needs to be performed by a highly trained expert. In order to assist the experts in the evaluation of cerebellar dimensions, we developed an automatic scheme for the segmentation of the 3D surface of the cerebellum in ultrasound volumes, using a spherical harmonics model. In this work, we present our validation results on 10 ultrasound volumes in which we have obtained an adequate accuracy in the segmentation of the cerebellum (mean Dice coefficient of 0.689). The method reported shows potential to effectively assist the experts in the assessment of fetal growth in ultrasound volumes.